2023
DOI: 10.1101/2023.11.14.567047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neopolyploidy-induced changes in the giant duckweed (Spirodela polyrhiza) alter herbivore preference, performance, and plant population performance

Hannah R. Assour,
Tia-Lynn Ashman,
Martin M. Turcotte

Abstract: PremisePolyploidy is a widespread mutational process in angiosperms that may alter population performance of not only plants but also their animal associates. Yet, knowledge of whether ploidy affects plant-herbivore dynamics is scarce. Here, we test whether aphid herbivores exhibit preference for diploid or neopolyploid plants, whether ploidy impacts plant and herbivore performance, and whether these interactions depend on plant genetic background.MethodsUsing multiple pairs of independently synthesized neotet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 86 publications
2
0
0
Order By: Relevance
“…Our results demonstrated that stress conditions can upend fitness differences between the ploidies. Large diploid population growth advantages under favorable (control) conditions ( Figures 1 and 2 ) corroborate previous studies with synthetic neopolyploid duckweeds ( Anneberg et al, 2023a ; Assour et al, 2023 ). However, here we showed that when exposed to pollutant stress, diploids were more similar to polyploids, and one contaminant (copper) even reversed the direction of the diploid–neopolyploid difference.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results demonstrated that stress conditions can upend fitness differences between the ploidies. Large diploid population growth advantages under favorable (control) conditions ( Figures 1 and 2 ) corroborate previous studies with synthetic neopolyploid duckweeds ( Anneberg et al, 2023a ; Assour et al, 2023 ). However, here we showed that when exposed to pollutant stress, diploids were more similar to polyploids, and one contaminant (copper) even reversed the direction of the diploid–neopolyploid difference.…”
Section: Discussionsupporting
confidence: 89%
“…This disconnect suggests that functional differences within diploid S. polyrhiza may derive from epigenetic variation that can be altered by autopolyploidization along with genetic variation ( Chen, 2007 ; Huber et al, 2021 ) and strongly influence stress tolerance and population growth. Regardless of the mechanism, our results join those of several others demonstrating the importance of genetic variation in diploid progenitors on neopolyploid morphology ( Wei et al, 2020 ), population growth ( Anneberg et al, 2023a ), and response to abiotic ( Bafort et al, 2023 ; Wei et al, 2020 ) and biotic interactions ( Anneberg et al, 2023b ; Assour et al, 2023 ; Forrester et al, 2020 ). They provide additional support for the idea that the repeated evolution of polyploids may be key to their success ( Kolář et al, 2017 ; Soltis & Soltis, 1999 ; Wei et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%